Aprendizagem por reforço profundo uma nova perspectiva sobre o problema dos k-servos - Lins, Ramon Augusto Sousa (2020)
The k-server problem in a weighted graph (or metric space) is defined by the need to efficiently move k servers to fulfill a sequence of requests that arise online at each graph node. This is perhaps the most influential online computation problem whose solution remains open, serving as an abstraction for a variety of applications, as buying and selling of currencies, reassign processes in a parallel processing for load balancing, online transportation service, probe management of oil production rigs, among others. Its conceptual simplicity contrasts with its computational complexity that grows exponentially with the increasing number of nodes and servers. Prior to this work, the Q-learning algorithm was used to solve small instances of the k-server problem. The solution was restricted to small dimensions of the problem because its storage structure grows exponentially with the increase in the number of nodes and servers. This problem, known as the curse of dimensionality, makes the algorithm inefficient or even impossible to execute for certain instances of the problem. To handle with larger dimensions, Q-learning together with the greedy algorithm were applied to a small number of nodes separated into different clusters (hierarchical approach). The local policy obtained from each cluster, together with greedy policy, were used to form a global policy satisfactorily addressing large instances of the problem. The results were compared to important algorithms in the literature, as the Work function, Harmonic and greedy. The solutions proposed so far emphasize the increase in the number of nodes, but if we analyze the growth of the storage structure defined by Cn,k ' O(nk) It can be seen that the increase in the number of servers can be quickly limited by the problem of the curse of dimensionality. To circumvent this barrier, the k-server problem was modeled as a deep reinforcement learning task whose state-action value function was defined by a multilayer perceptron neural network capable of extracting environmental information from images that encode the dynamics of the problem. The applicability of the proposed algorithm was illustrated in a case study in which different problem configurations were considered. The behavior of the agents was analyzed during the training phase and their performance was evaluated from performance tests that quantified the quality of the displacement policies of the servers generated. The results provide a promising insight into its use as an alternative solution to the k-servers problem.